Gynaecological Complications in General Surgery Unit: A Single-Center Study - Bhatti, Nadia; Bhatti, Afshan; Bhatti, Najia; Ali, Muharram; Shaikh, Aisha; Abro, Abdul Sattar (BioSight, 2022)
Introduction: This study aims to investigate the frequency of gynecological complications reported during emergency and elective general surgeries. Methodology: This is a cross-sectional study, data were collected retrospectively, approximately 500 patients went through surgical management in the general surgery department while only 125 reported associated issues requiring surgical management and required gynecological interventions. Data was entered & analyzed using SPSS version 22. Frequency and percentage were calculated for quantitative variables such as presenting complaints, reported gynecological issues, required intervention, and reported associated problems. Results: A total of 125 patients were enrolled in the study with the most commonly reported presenting complaint being pain with the vaginal discharge with vomiting documented in 72(57.5%) of patients. Puss discharge from wounds, peritonitis, and abdominal swelling were other frequently reported issues in 14(11.2%), 11 (8.7%), and 11 (8.7%) patients respectively. 98(78%) were discharged after successful management of gynecological as well as general surgical problems, 25(20%) were referred to tertiary care health care setup for more appropriate care and 1(1%) had a burst abdomen. Only 1 (1%) out of 125 patients expired during the study period. Conclusion: Gynecological complications have been markedly reported in the general surgery unit, necessitating general surgeons to intercede and deliver significant benefits in terms of lowering morbidity, mortality, postoperative complications, and length of hospital stay from a diagnostic and therapeutic point of view.